Immobilization of multivalent glycoprobes on gold surfaces for sensing proteins and macrophages - Gade, Madhuri; Khandelwal, Puneet; Sangabathuni, Sivakoti; Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Poddar, Pankaj; Kikkeri, Raghavendra (Analyst, 2016)
The multivalent display of carbohydrates on the cell surface provides cooperative binding to improve the specific biological events. In addition to multivalency, the spatial arrangement and orientation of sugars with respect to external stimuli also trigger carbohydrate-protein interactions. Herein, we report a non-covalent host-guest strategy to immobilize heptavalent glyco-beta-cyclodextrin on gold-coated glass slides to study multivalent carbohydrate-protein interactions. We have found that the localization of sugar entities on surfaces using beta-cyclodextrin (beta-CD) chemistry increased the avidity of carbohydrate-protein and carbohydrate-macrophage interactions compared to monovalent-beta-CD sugar coated surfaces. This platform is expected to be a promising tool to amplify the avidity of sugar-mediated interactions on surfaces and contribute to the development of next generation bio-medical products.